The Cyto-Genotoxicity Evaluation Of Biomedical Grade Chitosan On Primary Keratinocyte Cultures And Its Role In Scar Formation Pathways Using Skin Coculture Model - Lim , Chin Keong (2010)

(untitled)
Chitosan (-1, 4—D-glucosamine) is a deacetylated form of chitin with excellent biological properties useful in wound management. However, improvement of the physical and chemical properties of the chitosan will alter its biocompatibility. Additionally, chitosan has been reported to be useful in scar intervention. Therefore in this study, the in vitro biocompatibility of the modified chitosan porous skin regenerating templates (CPSRTs) has been evaluated based on cytotoxicity analysis by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay, genotoxicity by comet assay, and skin keratinocyte pro-inflammatory cytokine secretions [interleukin-1 (IL-1), tumor necrosis factor- (TNF-) and interleukin-8 (IL-8)], using primary normal human epidermal keratinocyte (pNHEK) cultures. The most biocompatible CPSRT was then investigated for its role in keloid intervention using keratinocyte-fibroblast cocultures. The human collagen type-I, III and V protein expressions were assayed in Western blot analysis.